PSYCHOLOGICAL CHARACTERISTICS OF AN INTERNET-DEPENDENT PERSONALITY - Mushkevych, Myroslava (PSYCHOLOGICAL JOURNAL, 2025)
The article explores the essence of Internet addiction and gadget dependence as a pressing socio-psychological phenomenon that has become widespread in the context of global digitalization. A comprehensive analysis is undertaken of the psychological profile of an Internet-dependent personality formed under the prolonged influence of virtual interaction. Internet addiction is defined as a multifaceted, dynamic construct manifesting in emotional dysregulation, decreased self-control, dominance of virtual over real-life interaction, and gradual transformation of personal values, orientations, and social attitudes. Internet addiction, as a form of non-chemical dependence, is presented as a psychologically hazardous compensatory behavior often arising from emotional deprivation, social isolation, anxiety, or low self-esteem. Special attention is given to the negative impact of excessive use of digital technologies on cognitive development, adaptation processes, sleep and eating patterns, and the emergence of dependent cognitive styles. The study emphasizes how Internet addiction alters the structure of the self-concept, reduces the level of reflection, complicates the identification process, and fosters pseudo-communicative habits that disrupt real-world social connections. Prolonged immersion in virtual environments leads to a deterioration in interpersonal skills, further intensifying feelings of loneliness, insecurity, and increasing the risk of anxiety and depressive disorders. The paper highlights the critical need for timely diagnosis, psychological correction, and prevention of Internet-dependent behavior, particularly among children, adolescents, and youth, as well as the importance of fostering digital competence as a key factor in psychological well-being in the information age.